Expected economic impacts of income tax in Saudi Arabia: Macroeconomic analysis - Al-Thumairy's, Imtithal Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aims to predict the macroeconomic effects of income tax in Saudi Arabia to diversify government income flows and increase non-oil government revenues. The research approach is based on using the dynamic general equilibrium model of the Saudi economy to achieve the results of simulating the scenario of applying income tax by 5% during the period (2020-2030). The results exhibit that income and profit tax reform showed positive results when transferring revenue through government transfers to households. A 5% income and profit tax are expected to improve GDP performance by 0.12%. Macroeconomic indicators, including consumption, investment, exports, and imports, are also improving slightly. Government revenues have enhanced due to the implementation of this scenario, and non-oil revenues are expected to increase from 370 billion Saudi riyals in 2020 to about 568 billion Saudi riyals in 2030. This will increase the contribution of non-oil revenues to total government revenues from 47% in 2020 to 57% in 2030. If income from income tax in the economy is transferred through government transfers to households, this will improve economic welfare.